The Effect of Biochar from Oil Palm Empty Fruit Bunches (EFB) on the Efficiency of Urea Fertilizer in the Production of Chinese Cabbage (Brassica rappa var. parachinesis L.) - Sisi Agustin; Agus Haryanto; Sugeng Triyono (Jurnal Agricultural Biosystem Engineering, 2023)
This research study aims to determine proper composition of biochar, to find out the efficiency of fertilizer used, and to evaluate the effect of interaction between biochar and urea fertilizer used on the cultivation of green mustard.  This study used Complete Randomized Design (CRD) consisting of 2 factors with factorial arrangement.  The first factor was biochar dosage consisting of: control (without biochar), 5 tons/ha, 7.5 tons/ha, and 10 tons/ha.  The second factor was urea dosage consisting of: control (without urea), 75 kg/ha, 125 kg/ha, and 200 kg/ha.  All treatment combinations were replicated 3 times so there were 48 experimental units obtained.  The parameters observed were: soil properties, biochar properties, plant height, leaf width, number of leaves, canopy area, shoot fresh weight, shoot dry weight, root fresh weight, root dry weight, total fresh weight, water consumption, water productivity, and fertilizer productivity.The addition of biochar is proven to increase the productivity of mustard plants. The use of urea fertilizer had no significant effect, presumably because of the low soil organic matter content. The interaction between biochar doses and urea fertilizer doses was not significant and only significant for the fertilizer productivity parameters. Research also revealed that the optimal dose of biochar for mustard greens is 5 tons/ha, giving an average yield of 88.25 g/plant and fertilizer productivity of 210.41%. Keywords: Biochar, Dose, Green Mustard, Oil Palm Empty Fruit Bunch (OPEFB), Urea Fertilizer.